2000
DOI: 10.1111/j.1365-3032.2000.00212.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in the patterns of feeding in fourth‐ and fifth‐instar Helicoverpa armigera caterpillars

Abstract: Summary Data are presented for developmental changes in feeding behaviour within and across the fourth and fifth stadium of Helicoverpa armigera (Lepidoptera, Noctuidae) caterpillars fed nutritionally homogeneous semi‐synthetic foods. We recorded the microstructure of feeding over continuous 12‐h periods on consecutive days throughout the two stadia, and in one experiment recorded continuously for 21 h. Larvae in the two stadia showed the same general pattern of macro‐events in feeding, including a similar dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…This could be due to changes in the nutritional requirements across instars. Older larvae of Lepidoptera have increased appetitive behaviour (Raubenheimer & Barton-Browne, 2000) and a need for more protein (Simpson et al, 1988). Blaney & Simmonds (1983) measured the quantity of an artificial diet eaten during the larval phase of H. armigera.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to changes in the nutritional requirements across instars. Older larvae of Lepidoptera have increased appetitive behaviour (Raubenheimer & Barton-Browne, 2000) and a need for more protein (Simpson et al, 1988). Blaney & Simmonds (1983) measured the quantity of an artificial diet eaten during the larval phase of H. armigera.…”
Section: Discussionmentioning
confidence: 99%
“…; Behmer ; Deans et al . ) including H. armigera (Raubenheimer & Browne ; Browne & Raubenheimer ; Tessnow et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, all nutrient choice experiments documented for Lepidoptera have been conducted exclusively on late or final instar caterpillars (Lee et al 2002;Lee et al 2004;Lee et al 2006;Behmer 2009;Deans et al 2015) including H. armigera (Raubenheimer & Browne 2000;Browne & Raubenheimer 2003;Tessnow et al 2018). It is not known whether nutrient choice differs between instars or whether early instars are capable of self-selecting their food.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on caterpillars, i.e. Manduca sexta (Reynolds et al 1986;Bernays & Woods 2000), Helicoverpa armigera (Raubenheimer & Barton-Browne 2000) and Bombyx mori caterpillars (Nagata & Nagasawa 2006) have shown that the pattern of feeding (i.e. the frequency and duration of meals) varies across foods types (Reynolds et al 1986;Timmins et al 1988;Bernays & Singer 1998) and can provide information about the insect´s physiological responses to food.…”
mentioning
confidence: 99%